2020
DOI: 10.1038/s41529-020-00145-2
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanisms controlling the residual corrosion rate of borosilicate glasses

Abstract: Borosilicate glasses are widely used to confine high-level radioactive wastes. The lifetime of these materials could reach hundreds of thousands of years if leaching of the glass into groundwater enables the formation of a passivating gel layer. Even in this regime, the glass will never stop corroding as thermodynamic equilibrium between glass and solution cannot be achieved. Therefore, accurate predictions of glass durability including passivation, require a deep understanding of the mechanisms controlling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 61 publications
4
43
0
Order By: Relevance
“…In the same context, a combination of DFT and NEB calculations indicate that the barrier energy for hydrolysis of B–O–B and B–O–Si bridges is much less than for Si–O–Si hydrolysis under acidic and neutral conditions, but this behavior is less pronounced under basic conditions . From experimental evidence, it was shown that under basic conditions and in dissolved silica, the hydrolysis of the B–O–Si bridges is rate limiting and has a slightly lower activation energy than for Si–O–Si hydrolysis . This may suggest that under acidic and neutral conditions, the dissolution of boron is faster than silicon (the release of boron will be much faster compared to silicon at low pH than at high pH).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same context, a combination of DFT and NEB calculations indicate that the barrier energy for hydrolysis of B–O–B and B–O–Si bridges is much less than for Si–O–Si hydrolysis under acidic and neutral conditions, but this behavior is less pronounced under basic conditions . From experimental evidence, it was shown that under basic conditions and in dissolved silica, the hydrolysis of the B–O–Si bridges is rate limiting and has a slightly lower activation energy than for Si–O–Si hydrolysis . This may suggest that under acidic and neutral conditions, the dissolution of boron is faster than silicon (the release of boron will be much faster compared to silicon at low pH than at high pH).…”
Section: Resultsmentioning
confidence: 99%
“…34 From experimental evidence, it was shown that under basic conditions and in dissolved silica, the hydrolysis of the B− O−Si bridges is rate limiting and has a slightly lower activation energy than for Si−O−Si hydrolysis. 89 This may suggest that under acidic and neutral conditions, the dissolution of boron is faster than silicon (the release of boron will be much faster compared to silicon at low pH than at high pH). However, as the previous studies did not take into account, on the one hand, two different kinds of boron units, namely, B III and B IV (see Table S2), and, on the other hand, the difference between the boron atoms of the same unit, understanding the boron release mechanism cannot be so simple (see Table 2).…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…Whether such a mechanism also applies in the basic pH range remains an open question. Whereas the formation of ASSLs in the basic pH range has been well documented for the weathering of borosilicate glasses (e.g., Gin et al, 2017Gin et al, , 2020, very few studies have investigated the chemical composition at the nm-scale of the near-surface region of dissolved olivine and pyroxenes in the basic pH range. Worthy of note, the spectroscopic characterizations of the surface composition of altered olivine performed by (Pokrovsky & Schott, 2000) suggested that ∼2 nm-thick ASSLs could be evidenced up to a pH of ∼9.…”
Section: Reactivity Of Olivine and Enstatite Controlled By Amorphous ...mentioning
confidence: 99%
“…The CJ4 composition was chosen for fabrication as the International Simple Glass (ISG) by the international nuclear waste glass community to study glass properties and durability behavior. 1,[55][56][57][58][59][60][61][62][63][64][65] A new series covering an extended Al compositional space based on the composition of ISG would provide valuable information regarding the effect of Al on long-term durability applicable to nuclear waste glasses.…”
Section: Decomposition Of Raman Spect On Glass Composition From Td Modelmentioning
confidence: 99%